2014
DOI: 10.12968/ajmw.2014.8.3.134
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of weight and weight awareness of patients presenting for outpatient care in Cameroon

Abstract: In Africa, the disease burden is changing with many populations now experiencing non-communicable diseases (NCDs) such as cardiovascular disease, hypertension, and diabetes. The worldwide association of obesity with an increase of NCDs has been well established. In African nations, the estimated obesity rates vary from 3.7 to 70.5%. This study aimed to identify: (1) the prevalence of obesity in the clinic user population and (2) the knowledge of and attitude toward obesity. The study population included 550 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
2
1
Order By: Relevance
“…When asked to identify their own body sizes using body image silhou- Matoti-Mvalo & Puoane, 2011;McCormick et al, 2014;Muhihi et al, 2012;Njecko, Meyer, Ashu, & Gobte, 2014;Puoane et al, 2005). Although our results matched these findings for overweight women, who tended to underestimate their current sizes, we conversely found that underweight women tended to overestimate their current sizes.…”
Section: Self-perception Of Body Sizecontrasting
confidence: 57%
See 2 more Smart Citations
“…When asked to identify their own body sizes using body image silhou- Matoti-Mvalo & Puoane, 2011;McCormick et al, 2014;Muhihi et al, 2012;Njecko, Meyer, Ashu, & Gobte, 2014;Puoane et al, 2005). Although our results matched these findings for overweight women, who tended to underestimate their current sizes, we conversely found that underweight women tended to overestimate their current sizes.…”
Section: Self-perception Of Body Sizecontrasting
confidence: 57%
“…Although most women chose figures that were within one BMI category of their actual figures (e.g., overweight women indicated normal weight figures), these slightly inaccurate self‐perceptions could have important health implications because overweight status is associated with increased risk for noncommunicable diseases (World Health Organization, ). Similar research studies across sub‐Saharan Africa have found that women tend to perceive their figures as smaller than their actual body sizes (Devanathan et al, ; Matoti‐Mvalo & Puoane, ; McCormick et al, ; Muhihi et al, ; Njecko, Meyer, Ashu, & Gobte, ; Puoane et al, ). Although our results matched these findings for overweight women, who tended to underestimate their current sizes, we conversely found that underweight women tended to overestimate their current sizes.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation